Assessment of Excessive Municipal Education Spending - Bartkus, Algirdas (Ekonomika, 2025)
A tight budgetary situation in Lithuania forces the Government to seek savings, plan financial resources carefully, and monitor their use closely. As a result, municipalities – which are responsible for implementing several delegated functions – are often viewed unfavourably by the central government when their spending appears excessive, and thus further widening the gap between the income and the expenditure. This article highlights one area where higher expenditure can be economically and strategically justified: education.The article examines the obstacles that prevent the economy from securing a well-qualified labour force, the measures that could strengthen the workforce quality, and the risks that arise when the economisation of education is applied uncritically. Failure to meet secondary school completion requirements remains a major barrier to full labour-market integration, limiting individuals’ long-term economic prospects and reducing the overall productivity of the workforce. Identifying factors within the education system that help reduce the number of early school leavers is therefore essential for improving labour-market outcomes and supporting sustainable economic development. Consequently, increased education spending directed toward targeted interventions – particularly those that help students complete secondary education – should not be interpreted as inefficiency. Instead, such investment represents a strategic measure that enhances human capital formation and contributes to stronger long-term economic performance.